Burkholderia thailandensis is virulent in Drosophila melanogaster. - Martina Pilátová; Marc S Dionne (PLoS ONE)
Melioidosis is a serious infectious disease endemic to Southeast Asia and Northern Australia. This disease is caused by the Gram-negative bacterium Burkholderia pseudomallei; Burkholderia thailandensis is a closely-related organism known to be avirulent in humans. B. thailandensis has not previously been used to infect Drosophila melanogaster. We examined the effect of B. thailandensis infection on fly survival, on antimicrobial peptide expression, and on phagocytic cells. In the fruit fly, which possesses only an innate immune system, B. thailandensis is highly virulent, causing rapid death when injected or fed. One intriguing aspect of this infection is its temperature dependence: infected flies maintained at 25°C exhibit rapid bacterial proliferation and death in a few days, while infected animals maintained at 18°C exhibit very slow bacterial proliferation and take weeks to die; this effect is due in part to differences in immune activity of the host. Death in this infection is likely due at least in part to a secreted toxin, as injection of flies with sterile B. thailandensis-conditioned medium is able to kill. B. thailandensis infection strongly induces the expression of antimicrobial peptides, but this is insufficient to inhibit bacterial proliferation in infected flies. Finally, the function of fly phagocytes is not affected by B. thailandensis infection. The high virulence of B. thailandensis in the fly suggests the possibility that this organism is a natural pathogen of one or more invertebrates.